Performance analysis and optimization of polarized on‐body relay channels. Issue 11 (21st April 2021) - Liu, Lingfeng; Jin, Jiabin; Zhang, Peng; Xia, Qin; Jiang, Nan; Liu, Zhiwei; Zhang, Xiaoyan
Abstract: On‐body propagation channels show significant polarization selectivity that has dominant impacts on the on‐body link quality in wireless body area networks. For on‐body relay channels over long distances across the body, the antenna polarization configurations of the relaying nodes are crucial to determine the relay performance, thereby requiring polarization optimization schemes. In this article, narrow band flat‐fading on‐body channels at 2.484 GHz are measured to analyse their polarization distribution above the skin under static postures. The measured on‐body channels show full‐space polarization convergence and dispersion, which are modelled by an extended 3 by 3 channel polarization matrix, and a statistical channel model is also proposed. Multi‐hop polarized on‐body relay channels are analysed on the relay link capacity, which shows polarization dependency between adjacent hop channels when relaying nodes are mounted by linearly polarized antennas. Both regular and iterative polarization selection algorithms are then designed to optimise the antenna polarization configuration of the nodes. Simulations based on the proposed polarization distribution model show significant link capacity increases for two‐hop and tfhree‐hop on‐body relay channels by the optimization algorithms. The results confirm the necessity of proper polarization selection schemes for on‐body relay channels.